2001
DOI: 10.1046/j.1365-2133.2001.04443.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of transforming growth factor-beta receptors type I and II by platelet-derived growth factor in human dermal fibroblasts

Abstract: These data suggest that PDGF receptor alpha and MAPK mediate stimulation of TGF-beta receptors by PDGF. Furthermore, TGF-beta receptor protein levels are discordantly regulated by PDGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(31 reference statements)
1
16
0
2
Order By: Relevance
“…This down-regulation was observed in the transcription activity of the human TGF␤RII promoter and in the mRNA and protein steady-state levels. Several cytokines and growth factors are known to regulate TGF␤ receptors, and discordant regulation of TGF␤RI and TGF␤RII has previously been reported (23,24). Ultraviolet irradiation has also been shown to modulate the expression of TGF␤RII without affecting the expression of TGF␤RI (25).…”
Section: Discussionmentioning
confidence: 92%
“…This down-regulation was observed in the transcription activity of the human TGF␤RII promoter and in the mRNA and protein steady-state levels. Several cytokines and growth factors are known to regulate TGF␤ receptors, and discordant regulation of TGF␤RI and TGF␤RII has previously been reported (23,24). Ultraviolet irradiation has also been shown to modulate the expression of TGF␤RII without affecting the expression of TGF␤RI (25).…”
Section: Discussionmentioning
confidence: 92%
“…However, we cannot exclude that HSC/myofibroblast activation may still depend on TGF-b signalling as PDGF-B was shown to upregulate TGF-b receptor I and II in vitro rendering these cells more susceptible to TGF-b [47]. One may speculate that at least part of the pro-fibrogenic effects of TGF-b could be mediated by PDGF-B, since TGF-b1 upregulates expression of both PDGF-B protein [48] and PDGF-B receptor [14].…”
Section: Discussionmentioning
confidence: 93%
“…There is evidence for a TGF-␤-dependent autocrine PDGF-A/PDGFR␣ signaling loop in sclerodermal skin and lung fibroblasts, suggesting a cross talk between TGF-␤ and the PDGF-A pathway (29). It has been reported that PDGF-A stimulates the expression of TGF-␤ receptors in human dermal fibroblasts (8). In the current study, we also tested the possible interaction between PDGF-D and TGF-␤.…”
mentioning
confidence: 80%